Manuresheds: Advancing nutrient recycling in US agriculture. (June 2020) - Spiegal, Sheri; Kleinman, Peter J.A.; Endale, Dinku M.; Bryant, Ray B.; Dell, Curtis; Goslee, Sarah; Meinen, Robert J.; Flynn, K. Colton; Baker, John M.; Browning, Dawn M.; McCarty, Greg; Bittman, Shabtai; et al.
Abstract: Nutrient recycling is fundamental to sustainable agricultural systems, but few mechanisms exist to ensure that surplus manure nutrients from animal feeding operations are transported for use on nutrient-deficient croplands. As a result, manure nutrients concentrate in locations where they can threaten environmental health and devalue manure as a fertilizer resource. This study advances the concept of the "manureshed" – the lands surrounding animal feeding operations onto which manure nutrients can be redistributed to meet environmental, production, and economic goals. Manuresheds can be managed at multiple scales, for example, on farms with both animals and crops, among animal farms and crop farms within a county, or even among animal farms and crop farms in distant counties. With a focus on redistribution among counties, we classified the 3109 counties of the contiguous United States by their capacity to either supply manure phosphorus (P) and nitrogen (N) from confined livestock production ("sources") or to assimilate and remove excess P and N via crops ("sinks"). Manure nutrient source counties were identified in 40 of the 48 states, with a substantial concentration in the southern US. Source counties for manure P greatly outnumbered source counties for manure N (390 vs. 100), and 99 of the 100 manure N source counties were also source counties for manure P. Conversely, sink counties for manure N outnumbered sink counties for manure P (2766 vs. 2317). We used the P balances of the source and sink counties to delineate four manuresheds dominated by various combinations of confined hog, poultry, dairy, and beef industries. The four manuresheds differed in the transport distances needed to assimilate excess manure P from their respective source areas (from 147 ± 51 km for a beef dominated manureshed to 368 ± 140 km for a poultry dominated manureshed), highlighting the need for systems-level strategies to promote manure nutrient recycling that operate across local, county, regional, and national scales. Highlights: A "manureshed" encompasses the lands surrounding animal feeding operations onto which manure nutrients can be redistributed to meet environmental, production, and economic goals. 3109 U.S. counties were classified as sources or sinks of manure nutrients. Manure nutrient source counties were found in 40 states. Manuresheds were delineated for major animal industries. Manureshed differed in transport distances from 147 km to 368 km.